Fine the derivative of
![y = 4x - 8 \div 3x + 11 \\ y = {x}^{2} \div {x}^{3} + 1 \\ y = 1 + {x}^{2} - x \div 1 - {x}^{2} + x y = 4x - 8 \div 3x + 11 \\ y = {x}^{2} \div {x}^{3} + 1 \\ y = 1 + {x}^{2} - x \div 1 - {x}^{2} + x](https://tex.z-dn.net/?f=y+%3D+4x+-+8+%5Cdiv+3x+%2B+11+%5C%5C+y+%3D++%7Bx%7D%5E%7B2%7D++%5Cdiv++%7Bx%7D%5E%7B3%7D++%2B+1+%5C%5C+y+%3D+1+%2B++%7Bx%7D%5E%7B2%7D++-+x++%5Cdiv+1+-++%7Bx%7D%5E%7B2%7D++%2B+x)
Answers
Answered by
1
- ANSWER IS GIVEN AT END IN EACH PART.
- EACH STEP IS EXPLAINED CAREFULLY !
Step-by-step explanation:
(i) y=
Now, (by applying dividing rule)
⇒
⇒
⇒(∵ Both 12x will cancel eachother)
Hence, this is the answer.
(ii)y=
Now,(by applying dividing rule)
⇒
⇒
⇒
Hence, this is the answer.
(iii)y=
Now, (by applying dividing rule)
⇒
⇒
⇒
⇒
⇒ (∵ both
and
will cancel out eachother)
Hence, this is the answer.
MARK ME AS BRAINLIEST... ;)
Similar questions